2019
DOI: 10.1177/1753425919881176
|View full text |Cite
|
Sign up to set email alerts
|

Role of neutrophils in tuberculosis: A bird's eye view

Abstract: Neutrophils are innate immune cells implicated in the process of killing Mycobacterium tuberculosis early during infection. Once the mycobacteria enter the human system, neutrophils sense and engulf them. By secreting bactericidal enzymes and α-defensins like human neutrophil peptides loaded in their granule armory, neutrophils kill the pathogen. Peripheral blood neutrophils secrete a wide range of cytokines like IL-8, IL-1-β and IFN-γ in response to mycobacterial infection. Thus they signal and activate dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 66 publications
(62 reference statements)
1
41
0
2
Order By: Relevance
“…The effector mechanisms of IL-17A are diverse and can contribute to protection in a number of ways. For example, expression of antimicrobial β-defensin-2 by airway epithelial cells is upregulated after experimental IL-17 treatment, 35 and IL-17A is also known to be involved in neutrophil recruitment to the lungs, which, in turn, has been implied in early protection from TB. 37 , 38 , 39 Additionally, it has been demonstrated that IL-17A is involved in early control of Mtb and formation of protective lymphoid follicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effector mechanisms of IL-17A are diverse and can contribute to protection in a number of ways. For example, expression of antimicrobial β-defensin-2 by airway epithelial cells is upregulated after experimental IL-17 treatment, 35 and IL-17A is also known to be involved in neutrophil recruitment to the lungs, which, in turn, has been implied in early protection from TB. 37 , 38 , 39 Additionally, it has been demonstrated that IL-17A is involved in early control of Mtb and formation of protective lymphoid follicles.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of antimicrobial b-defensin-2 by airway epithelial cells is upregulated after experimental IL-17 treatment, 35 and IL-17A is also known to be involved in neutrophil recruitment to the lungs, which, in turn, has been implied in early protection from TB. [36][37][38] Additionally, it has been demonstrated that IL-17A is involved in early control of Mtb and formation of protective lymphoid follicles. 32,39 However, despite evidence of the protective effect of IL-17A in preclinical models, its precise role in human TB remains to be resolved and is likely dependent on factors such as time, location, and magnitude of IL-17A production as well as conditions of comorbidity and coinfection, including HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil accumulation in Mtb infection leads to inflammation and has been shown to be detrimental to the host [27,45]. Aggregated Mtb infection led to neutrophil accumulation in a mouse model [11].…”
Section: Discussionmentioning
confidence: 99%
“…bovis infected mice, which also correlates with higher neutrophil infiltration in the total lung cell population. Increased neutrophilia has been previously related to exacerbation of TB pathology and poor prognosis, and a neutrophil-driven IFN-inducible transcript signature in human whole blood of patients with active TB correlates with clinical severity [ 23 , 25 , 26 , 42 ]. Here we show that lung neutrophilia and increased numbers of infected neutrophils in the lung correlate with enhanced pathology, higher bacterial burden and dissemination in M .…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the enhanced virulence phenotype of the M. bovis strain, we found a strongly increased neutrophil influx in this group (Fig 2G and 2H). Interestingly, different studies have shown an association, both in humans and animal models, between an increase of neutrophil infiltration in the lungs and a higher degree of TB disease [23][24][25][26].…”
Section: Bovis Disseminates More Efficiently Than M Tuberculosis mentioning
confidence: 99%